Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0014-5793(00)02012-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulation of somatostatin receptor subtypes: differential effects on Ras/MAP kinase pathway and cell proliferation in human neuroblastoma cells

Abstract: In previous studies we have showed that somatostatin (SST) inhibits cell division, mitogen-activated protein (MAP) kinase and Ras activity in the human neuroblastoma cell line SY5Y. In the present study, we have assessed the role of a series of SST analogs, three of which were selective for SSTR1, SSTR2 or SSTR5, in these cellular events. All the analogs inhibited forskolin-induced cAMP accumulation. Selective stimulation of SSTR1 or SSTR2 but not of SSTR5 inhibited platelet-derived growth factor (PDGF)-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
39
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 19 publications
(31 reference statements)
4
39
0
3
Order By: Relevance
“…It has been suggested that somatostatin receptor (SSTR) expression is a favorable prognostic factor in human neuroblastoma because high levels of SSTR type 2 positively relate to patient survival (9,10). In previous studies, we have shown that somatostatin inhibits proliferation, ERK 1/2 and Ras activity in SH-SY5Y cells (11,12), and that these cells express all five SSTR subtypes (13). Moreover, it has also been reported that somatostatin can inhibit human endothelial-like EAhy926 cell invasion and monocyte migration (14), and these effects have been related to its ability to impair the angiogenic process.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It has been suggested that somatostatin receptor (SSTR) expression is a favorable prognostic factor in human neuroblastoma because high levels of SSTR type 2 positively relate to patient survival (9,10). In previous studies, we have shown that somatostatin inhibits proliferation, ERK 1/2 and Ras activity in SH-SY5Y cells (11,12), and that these cells express all five SSTR subtypes (13). Moreover, it has also been reported that somatostatin can inhibit human endothelial-like EAhy926 cell invasion and monocyte migration (14), and these effects have been related to its ability to impair the angiogenic process.…”
mentioning
confidence: 86%
“…To verify whether somatostatin possesses anti-migratory and anti-invasive properties, we studied its effects on PDGF-induced motility and invasion in SH-SY5Y cells, previously characterized in our laboratory for the expression of multiple SSTR subtypes (13). Pretreatment of the cells with somatostatin inhibited the migration and invasion induced by PDGF 20 ng/ml in a concentration-dependent manner (Fig.…”
Section: Pdgf-stimulated Motility and Invasiveness In Sh-sy5ymentioning
confidence: 99%
“…The two peptides produced by SST cells act as neurotransmitters or paracrine/ autocrine regulators via five different subtypes of human SSTRs (SSTR1-5), encoded by five distinct SSTR genes segregated on chromosome 14,16,17,20,22 [1]. The highest homology of hSSTRs have been found in their transmembrane domains (TM), with a highly conserved sequence, YANSCANPI/ VLY, in the seventh TM, found in all human SSTRs as well as in other species [2].…”
mentioning
confidence: 99%
“…Nonetheless, the detailed mechanisms of the SSTRmediated inhibition of tumor growth remain to be further investigated. Also, intracellular pathways involved in SSTR signaling may need to be studied in each individual case since subtype-and cell typespecific signaling components have been reported [1,14]. However, despite of the contradictory information obtained in different cell types using different SST analogues, it is generally accepted that all five SSTR subtypes are coupled to inhibition of the adenylyl cyclase-cAMP pathway and stimulate phosphotyrosyl protein phosphatase (PTP) [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation